Relevance of the ART method for the teaching of the Latin American story in Elementary school (EGB) - Román, Andrés Eduardo (2020)
The ARTE method is a set of reflexive, theoretical and experimental activities based on the learning theories of Piaget, Vygotsky and Ausubel. The methodology used for the research was qualitative, bearing in mind that it is a humanistic researchabout thediversification of the classroom. The relevance and importance of this method is evident throughout the methodological process of the research taking into consideration the integration that took place between the pre-professional practices of the school year and the compilation of theoretical foundations. The ARTE method within its evaluation process recognizes diversity and dialogue as the main actors and foundations for improving the quality of the education system, since the student is given autonomy and awareness of the processes in all their dimensions.